مفهوم العقاب الالهي في القران الكريم (دراسة تحليلية وتفسيرية) - عكاب, حيدر خزعل فهد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research aims to study the concept of divine punishment in the Holy Quran through an analytical and interpretive approach that combines linguistic, legal and objective understanding of Quranic verses related to punishment. The research deals with the types of divine punishment, its causes and objectives, with a focus on the educational, social and spiritual dimensions of punishment within the framework of Islamic law. The research presents the different classifications of punishment, including worldly and otherworldly punishment, individual and collective punishment, with an analysis of Quranic examples for each type. The research also reviews the concept of divine justice and the balance of mercy and punishment, and how to achieve a balance between intimidation and encouragement in Quranic discourse. Through the interpretive study, the research relies on the opinions of ancient and contemporary interpreters, with a focus on the purposes of punishment and its impact on correcting human behavior and controlling societies. The research also discusses the issue of repentance and forgiveness and their role in avoiding or mitigating punishment. The research concludes that divine punishment in the Holy Quran is not merely a punishment for sins, but rather a divine means to reform individuals and societies and achieve divine justice, and reflects God’s mercy and wisdom in managing the affairs of creation